2016
DOI: 10.2319/111315-766.1
|View full text |Cite
|
Sign up to set email alerts
|

Facial soft-tissue changes after rapid maxillary expansion analyzed with 3-dimensional stereophotogrammetry: A randomized, controlled clinical trial

Abstract: Objective: To evaluate three-dimensional (3-D) soft tissue facial changes following rapid maxillary expansion (RME) and to compare these changes with an untreated control group. Materials and Methods: Patients who need RME as a part of their orthodontic treatment were randomly divided into two groups of 17 patients each. Eligibility criteria included having maxillary transverse deficiency with crossbite, and to be in the normal range according to body mass index. In the first group (mean age  = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…The aim of the present RCT was to evaluate long‐term effects on facial soft tissue produced by RME treatment. Baysal et al recently published an RCT showing nonsignificant differences in soft tissue changes with RME treatment after 6‐month retention in the treated group compared with control, except for alar base width that increased of approximately 1 mm in treated subjects after treatment. In the present study, alar base width increased 1.98 mm in treated group compared with control, but the difference might not be clinically significant in the impact of the whole face, even though a large effect was detected between the groups for this variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the present RCT was to evaluate long‐term effects on facial soft tissue produced by RME treatment. Baysal et al recently published an RCT showing nonsignificant differences in soft tissue changes with RME treatment after 6‐month retention in the treated group compared with control, except for alar base width that increased of approximately 1 mm in treated subjects after treatment. In the present study, alar base width increased 1.98 mm in treated group compared with control, but the difference might not be clinically significant in the impact of the whole face, even though a large effect was detected between the groups for this variable.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, RME was suggested to promote a transitory increase in skeletal vertical dimension of the face due to downward and backward rotation of the mandible . Baysal et al showed significant downward and backward displacement of pogonion, even if bonded acrylic splint expander was employed in order to prevent the bite opening effects. In the present investigation, an expander with bands on the upper primary teeth was employed and no significant differences in the face heights were reported between treated and control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the technique has been used to report on basal facial surface symmetry . Stereophotogrammetry has also been used to assess facial morphology on adults with unilateral cleft lip and palate, and the effects of orthodontic treatment undertaken by rapid maxillary expansion . In relation to the rehabilitation of individuals with hemifacial microsomia, a stereophotogrammetry technique has been used to predict the position and size of an artificial ear on the face …”
mentioning
confidence: 99%